2010
DOI: 10.32607/20758251-2010-2-1-97-101
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Formate Dehydrogenase Stress Stability in vivo using Inactivation by Hydrogen Peroxide

Abstract: Kinetic studies on hydrogen peroxide–induced inactivation of mutant formate dehydrogenase from Pseudomonas sp. 101 (PseFDH Cys255Ala) suggest a simple bimolecular mechanism for enzyme reaction with the inactivation agent. In the excess of hydrogen peroxide, the decrease in enzyme activity follows first–order kinetics. Therefore, the first–order effective inactivation kinetic constants determined for various FDH forms at a constant H2O2 concentration can be used as a quantitative measure of the enzyme stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
0
9
0
3
Order By: Relevance
“…The poor stability of native cb FDH was well documented in the literature, which was prone to thermal deactivation at >40 °C and chemical instability against chemicals, which can influence the stability of tertiary and quaternary structures. Cysteine residues are the most critical residues responsible for stability, and hence, oxidation of the cysteine thiol group possibly leads to enzyme deactivation . The use of PEI has been demonstrated to have a positive effect on enzyme activity and stability on enzymes like glucose dehydrogenase, lactate dehydrogenase, alcohol dehydrogenase, and β-galactosidase. Lin et al have reported PEI-grafted graphene oxide as a novel scaffold for immobilization for cb FDH, which showed 47.4% activity after eight times repeated use, in addition to having 2.4-fold activity as compared to that of an enzyme immobilized on plain graphene oxide …”
Section: Results and Discussionmentioning
confidence: 99%
“…The poor stability of native cb FDH was well documented in the literature, which was prone to thermal deactivation at >40 °C and chemical instability against chemicals, which can influence the stability of tertiary and quaternary structures. Cysteine residues are the most critical residues responsible for stability, and hence, oxidation of the cysteine thiol group possibly leads to enzyme deactivation . The use of PEI has been demonstrated to have a positive effect on enzyme activity and stability on enzymes like glucose dehydrogenase, lactate dehydrogenase, alcohol dehydrogenase, and β-galactosidase. Lin et al have reported PEI-grafted graphene oxide as a novel scaffold for immobilization for cb FDH, which showed 47.4% activity after eight times repeated use, in addition to having 2.4-fold activity as compared to that of an enzyme immobilized on plain graphene oxide …”
Section: Results and Discussionmentioning
confidence: 99%
“…The C255A replacement results in preservation of 60% of the enzyme activity after 90-day storage at 25°C, whereas the wild-type PseFDH becomes completely inactive at this point [ 14 ]. The double replacement C145S/C255A decreases the enzyme inactivation rate constant in the presence of 100 mM hydrogen peroxide by almost 100 times [ 15 ]. The A198G replacement provides a decrease in structural tension in the polypeptide chain turn connecting βA beta-sheet and αB helix in the coenzyme binding domain of PseFDH active site.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of N-terminal His-tag on the properties of the wild-type enzyme and its NADP + -specific mutants has been studied by site-directed mutagenesis [ 13 ]. Chemical stability of PseFDH has been improved as well, and the mutants with an increased stability in the presence of hydrogen peroxide have been produced [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mutation A198G improves the binding of NADP + when cofactor specificity has already changed: e.g., by the D221Q mutation . The third residue is C255, which interacts with the adenine moiety of NAD + , and its mutation to valine was shown to improve the binding affinity toward NADP + . Similarly, the NADP + -dependent FDH from Burkholderia spp.…”
Section: Resultsmentioning
confidence: 99%